Analysis Of The Socioeconomic And Environmental Impacts Of Irrigated Agriculture In The Irrigated Perimeter Of Pau Dos Ferros (Rn) - Almeida, José Jobson Garcia de; Costa, Franklin Roberto (Geografares, 2014)
The Brazilian Government implemented irrigated perimeters to ameliorate problems of drought and poverty in the Northeast. In this sense, the objective of this work was to analyze the social, economic and environmental impacts generated by the practice of irrigated agriculture in the municipality of Pau dos Ferros-RN, resulting from the impacts caused by the activity. Obtained references on the topic, on-site visits and interviews with producers of the perimeter. It was observed the presence of negative impacts in the area, such as waste, contamination and water salinisation, compaction and soil erosion, deforestation caused by the removal of the native vegetation, high consumption of energy and public health problems.